Information technology and social sciences: how can health IT be used to support the health professional?. Issue 1 (16th September 2016) - Wagner‐Menghin, Michaela; Pokieser, Peter
Abstract : Keeping up to date with the increasing amount of health‐related knowledge and managing the increasing numbers of patients with more complex clinical problems is a challenge for healthcare professionals and healthcare systems. Health IT applications, such as electronic health records or decision‐support systems, are meant to support both professionals and their support systems. However, for physicians using these applications, the applications often cause new problems, such as the impracticality of their use in clinical practice. This review adopts a social sciences perspective to understand these problems and derive suggestions for further development. Indeed, humans use tools to remediate the brain's weaknesses and enhance thinking. Available health IT tools have been shaped to fit administrative needs rather than physicians' needs. To increase the beneficial effect of health IT applications in health care, clinicians' style of thinking and their learning needs must be considered when designing and implementing such systems. New health IT tools must be shaped to fit health professionals' needs. To further ease the integration of new health IT tools into clinical practice, we must also consider the effects of implementing new tools on the wider social framework.